2018
DOI: 10.23822/eurannaci.1764-1489.48
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota profile in atopic asthmatic adult patients

Abstract: Studies proposed a link between gut microbiota and airway tract. Study the diversity and density of gut microbiota in healthy and asthmatic patients. Semi-quantitative stool cultures were performed from fecal samples collected from 80 adult asthmatic patients and 40 healthy individuals. Data on gender, age, dietetic history, clinical examination and investigations as skin prick test and pulmonary function testing were also collected. were found to be higher among patient group than control group. density was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…This might be due to the complicated intestinal microbiome of adults, requiring consideration of diverse host factors, such as living environment and diet. Recently, the distinct gut microbiota has also been revealed in adult asthmatics 26,27 . Supporting this phenomenon, microbe-derived short-chain fatty acids were suggested as possible mediators in the pathogenesis of asthma 28 .…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the complicated intestinal microbiome of adults, requiring consideration of diverse host factors, such as living environment and diet. Recently, the distinct gut microbiota has also been revealed in adult asthmatics 26,27 . Supporting this phenomenon, microbe-derived short-chain fatty acids were suggested as possible mediators in the pathogenesis of asthma 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Further studies on the fecal microbiota profile of adult atopic asthmatic patients revealed a positive association between Lactobacilli and Escherichia coli ( E . coli ) and atopic asthma as compared with healthy individuals 53 . In addition, another study revealed a negative association of Bifidobacterium adolescentis with long‐term asthma and a positive association of the Bifidobacterium adolescentis with total IgE levels in adult asthmatic patients 54 .…”
Section: Impact Of the Intestinal Microbiota On Allergymentioning
confidence: 95%
“…51 Further studies on the fecal microbiota profile of adult atopic asthmatic patients revealed a positive association between Lactobacilli and Escherichia coli (E. coli) and atopic asthma as compared with healthy individuals. 53 In addition, another study revealed a negative association of Bifidobacterium adolescentis with long-term asthma and a positive association of the Bifidobacterium adolescentis with total IgE levels in adult asthmatic patients. 54 In this respect, gut microbiome analysis in adults with allergic rhinitis compared with healthy controls demonstrated a reduction in αdiversity measured by the Shannon index with more abundance of Bacteroidota such as Parabacteroides and less abundance of phylum Firmicutes such as Coprococcus.…”
Section: Key Messagementioning
confidence: 97%
“…Several studies reinforce the concept that dysbiosis is heavily linked to allergic disease, especially asthma. Individuals with atopic asthma have significantly higher fecal levels of Lactobacillus and E. coli compared with healthy individuals [366]. In terms of microbiota metabolites, 12,13-diHOME (a relatively uncharacterized linoleic acid) is commonly found in neonates at high risk for asthma [367].…”
Section: Allergic Diseasesmentioning
confidence: 99%